1991
DOI: 10.1002/bjs.1800780408
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared spectroscopy in peripheral vascular disease

Abstract: Near-infrared spectroscopy has been performed on the calf muscles of 38 subjects, 21 normal controls without vascular disease and 17 patients with peripheral vascular disease. Oxygen consumption was measured in the calf by calculating the rate of conversion of oxyhaemoglobin to deoxyhaemoglobin during a period of tourniquet-induced ischaemia. Postischaemic reoxygenation was also measured. Median oxygen consumption in patients with peripheral vascular disease was 0.10 ml 100 g tissue-1 min-1, while in the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
102
2
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(117 citation statements)
references
References 21 publications
11
102
2
2
Order By: Relevance
“…A possible explanation for this observation is a redistribution of blood in the calf muscle during arterial occlusion. Increase of tHb during arterial occlusion was also found in other studies [13,14].…”
Section: Abi Recovery Times Compared To Nirs Recovery Timessupporting
confidence: 86%
See 2 more Smart Citations
“…A possible explanation for this observation is a redistribution of blood in the calf muscle during arterial occlusion. Increase of tHb during arterial occlusion was also found in other studies [13,14].…”
Section: Abi Recovery Times Compared To Nirs Recovery Timessupporting
confidence: 86%
“…In contrast, Cheatle et al [14] found a reduced V02 at rest in claudicants. A possible explanation for this difference is that the claudicants in the present study had not totally recov ered from the walking exercise when arterial occlusion started, which may have overestimated V02 at rest, V02 after walking exercise is more increased in claudi cants than in nonclaudicants.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Reported values of muscle oxygen consumption at rest are in the range 1.8-12.3 mol/100 ml/min. 5,14 By measuring at rest we mean that the protocol does not involve the application of any particular stress to the measured tissue. In measurements at rest, the subject is lying or sitting motionless and no exercise is required.…”
Section: Introductionmentioning
confidence: 99%
“…NIRS blood flows for resting and post-exercise s h o w g o o d a g r e e m e n t w i t h s t r a i n -g a u g e plethysmography 21,32) , although flow measured by plethysmography is generally two to three times higher than the NIRS flow 21,24) . On the other hand, VO 2NIRS using arterial occlusion can be calculated from the rate of decrease in OxyHb [37][38][39][40] or from the rate of decrease in Hbdiff, reflecting the difference between oxyand deoxyhaemoglobin (Hbdiff) 2 0, 22 -2 4, 37 ) . VO 2NIRS during rest proved to be reproducible within one test session 2 3 ) and between test sessions 41) .…”
Section: Discussionmentioning
confidence: 99%